Pengantar Perencanaan Pendidikan Islam - Binti Muarifatul Maulidia; Muhammad Yahya Ashari (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2023)
Abstract. Planning will be considered mature and good if it meets the requirements and elements in the planning itself. However, in reality, the planning element is only used as a complementary factor in the leader's policy explanation. This article was prepared to explain the meaning, role and function of educational planning. The method used in this research is library research. The data collected is in accordance with discussions originating from books, journals, etc. When preparing plans, it is necessary to pay attention to the following things: relating to the future; a set of activities; systematic process; specific results and goals. The function and role of educational planning are: It is the motto for implementing educational development activities, It is a means of controlling the implementation of educational development, It is a tool for ensuring the quality of educational development.